ANALISIS KETERLAKSANAAN PRAKTIKUM BIOLOGI TERHADAP HASIL BELAJAR PSIKOMOTORIK SISWA KELAS X IPA DI SMA NU JUNTINYUAT INDRAMAYU - Sari, Yuli Arnita (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2024)
This research aims to determine the implementation of biology learning practicum for class X IPA SMA NU Juntinyuat Indramayu. This research is a qualitative descriptive study, with the research sample being students of class X IPA SMA NU Juntinyuat Indramayu taken by random sampling with a total of 55 students. The data collection technique was carried out using an observation questionnaire on student’s psychomotor activities in practicum activities, then the data was analyzed using descriptive statistics. The results of the research showed that the results of the questionnaire for implementing practicum activities had been implemented properly, were 75.75, the results of the psychomotor assessment in the group were 76.6, with good criteria, while the results of interviews with informants showed that some information about biology practicum planning was not in accordance with the current curriculum. because there are several obstacles.